Second-hand smoke in four English prisons: an air quality monitoring study - Jayes, Leah; Ratschen, Elena; Murray, Rachael L.; Dymond-White, Suzy; Britton, John (BioMed Central, 2016)
BACKGROUND: To measure levels of indoor pollution in relation to smoking in four English prisons. METHODS: TSI SidePak AM510 Personal Aerosol Monitors were used to measure concentrations of particulate matter less than 2.5 mum in diameter (PM2.5) for periods of up to 9 h in selected smoking and non-smoking areas, and personal exposure monitoring of prison staff during a work shift, in four prisons. RESULTS: PM2.5 data were collected for average periods of 6.5 h from 48 locations on 25 wing landings where smoking was permitted in cells, on 5 non-smoking wings, 13 prisoner cells, and personal monitoring of 22 staff members. Arithmetic mean PM2.5 concentrations were significantly higher on smoking than non-smoking wing landings (43.9 mug/m(3) and 5.9 mug/m(3) respectively, p < 0.001) and in smoking than non-smoking cells (226.2 mug/m(3) and 17.0 mug/m(3) respectively, p < 0.001). Staff members wore monitors for an average of 4.18 h, during which they were exposed to arithmetic mean PM2.5 concentration of 23.5 mug/m(3). CONCLUSIONS: The concentration of PM2.5 pollution in smoking areas of prisons are extremely high. Smoking in prisons therefore represents a significant health hazard to prisoners and staff members.